The analysis of the International Practice of Realization and Financing of Projects of Public-Private Partnership in Development of Regional Infrastructure - Sergey Valentinovich Kelbakh; Maria Viktorovna Sigova (Управленческое консультирование)
In the article, the analysis of the international practice of realization and resource providing projects of the public-private partnership is carried out. Distributions of the public-private partnership projects on branches in the countries with the different level of economic development is described. Organizational and economic mechanisms of realization of public-private partnership in such countries as Great Britain, Australia, Ireland, Brazil and China is revealed.